Capturing light : the heart of photography - Freeman, Michael, 1945- (Focal Press, Taylor & Francis Group, 2013)
"For professional photographers, chasing the light, waiting for it, sometimes helping it, and finally capturing it is a constant preoccupation- and for some, an obsession. Drawing on four decades of working with light, Michael Freeman takes a simple but practical approach to interpreting, reacting to, and capturing photography's most valuable commodity."--Back cover.